A Prospective Evaluation of the Effect of Supervised Hand Therapy After Carpal Tunnel Surgery. (May 2020) - Gil, Joseph A.; Weiss, Barrett; Kleiner, Justin; Akelman, Edward; Weiss, Arnold-Peter C.
Background: The objective of this investigation is to examine the effect of postoperative therapy after routine carpal tunnel release. Our hypothesis was that supervised hand therapy does not improve outcomes after routine carpal tunnel release.Methods : Patients with carpal tunnel syndrome were randomly assigned to one of 3 groups based on the last digit of their medical record numbers to one of 3 groups: standard 6-week postoperative rehabilitation (standard therapy), expedited one-session postoperative rehabilitation group (expedited therapy), and no postoperative rehabilitation group (no therapy). The primary outcome measures were Quick Disabilities of the Arm, Shoulder, and Hand (QuickDASH) and return to work. The outcome questionnaire was completed preoperatively, at the 2-week follow-up visit, and monthly to 6 months after surgery.Results: All 3 treatment groups had similar mean QuickDASH scores preoperatively. At 1- to 6-month follow-up, all 3 groups had similar QuickDASH scores at each visit, and all showed a significant decline from baseline (preoperative) QuickDASH score. Overall, QuickDASH score decreased significantly from a preoperative visit mean of 42.7 to a final postoperative (visit 8) mean of 6.69. There was no significant difference in the mean QuickDASH score among all 3 groups at 6-month follow-up. There was no significance in the time of return to work among the 3 groups (standard therapy, 21.8 days; expedited therapy, 20.9 days; no therapy, 16.6 days).Conclusions : This investigation adds evidence that supervised hand therapy does not improve the outcomes of routine carpal tunnel surgery as measured by QuickDASH and return to work.